Cosmocentric and Deep Ecology Movement: An Extreme Web of Valuing Nature - Kemi Anthony Emina (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
The core concern in environmental ethics is non-anthropocentrism, and the pursuit of environmental justice would be an unproductive endeavour without addressing this concept. The feasibility of non-anthropocentrism, strictly defined, poses a significant challenge. The consideration of the Deep Ecology movement, without engaging in circular reasoning, allows for the contemplation of non-anthropocentrism. However, it is widely speculated that the implementation of a Deep Ecology initiative is a plausible option. The philosophical framework of deep ecology is characterised as having metaphysical underpinnings. Environmental ethics are inherently practical and have real-world applications. However, the subject matter of environmental ethics has transitioned from the metaphysical realm. A major issue that ensues pertains to the potential incongruity between the Deep Ecology movement, which can be characterised as a metaphysical or ontological theoretical framework that is non-anthropocentric in its nature, and environmental ethics, which is primarily concerned with practical and applied aspects. Given the metaphysical nature of deep ecology, the question arises as to how it aligns with practical or applied ethics. Numerous scholars believe that, within the realm of environmental ethics, deep ecology, or cosmocentrism, lacks substantial pertinence. Cosmocentrism can be characterised as having metaphysical or ontological foundations. This study aims to investigate the concept of cosmocentrism as a fundamental aspect of promoting environmental justice. The term “extreme” is applicable in this context since it delineates the boundaries of environmental ethics.